As representações da violência na região do contestado entre o Espírito Santo e Minas Gerais (1940-1962) - Silva, Edmilton da (2019)
The history of the disputed region between Espírito Santo and Minas Gerais (a Contestado) arose more prominently at the dawn of the XIX century with the 1800 Auto and only ended in 1963 with the Bananal Agreement, which was signed between the governors of both litigating states. The territorial and political jurisdiction disputes and between Minas and Espírito Santo almost led their Military Police forces to an armed conflagration in the region. In addition to the territorial dispute, the Mineiro-Capixaba Contestado was marked, essentially, as picture of violence around the possession and use of the land, especially after it acquired value as a capital good and was put on the market as any another commodity. Violence was exacerbated from the 1940s and on when the Contestado suffered a great demographic explosion that occurred after farmers and landgrabbers arrived in the region and, with the services of jagunços and gunmens, sought to usurp the right of squatters who had first occupied the land and put their workforce and hopes for better living conditions. In this fight there was, among others, the support of the Military Police force of Espírito Santo, who through various diligences – some visibly illegal – favored the strongest and most powerful side. This situation reached greater prominence in the municipality of Ecoporanga, where the peasants struggle presented more brutal contours and the squatters – that were almost always represented as invaders, rioters and criminals, in the end, as a “dangerous class” – suffered more persecution. Thus, through oral history as a methodology, as well as through Critical Discourse Studies, we aim to study the representations of violence in the disputed region in the period between 1940 and 1962. In particular, we investigated whether such representations would have contributed to stimulating and aggravating the conflicts in which the various social actors (squatters, military police force, landowners, landgrabbers, jagunços and gunmen, among others) were involved, leading to a setting of extreme violence in that region. In this way, we noticed that in the North of the State, and especially in the contested region, there was a common repertoire of representations that produced and stimulated a series of tensions and conflicts between the social actors involved, having violence mainly against people the most obvious and cruel outcome. We also note that this violence is an integral part of the human condition itself and of life in society. In fact, of a society that, at least in the Contestado, has revealed itself as being dynamic, violent and unjust and in a transformation process.